Veronica Mars, fandom, and the 'Affective Economics' of crowdfunding poachers. (February 2015) - Hills, Matt
This article considers 'affective economics' in relation to the phenomenon of crowdfunding. It focuses on 'fan-ancing', where media fans are targeted by crowdfunding campaigns. Returning to Henry Jenkins' work enables consideration of how Veronica Mars' creator Rob Thomas has enacted a kind of affective economics by positioning himself as a fan-like showrunner, resistant to commercial/official industry practices, thereby according with Kevin Roberts' notion of 'lovemarks', as well as discursively prefiguring Thomas' use of Kickstarter for the Veronica Mars movie campaign in 2013. Taking this specific Kickstarter as a case study, I also theorise Veronica Mars' fan-consumers as 'crowdfunding poachers' who made the Kickstarter meaningful in relation to their own fan identities at the same time as willingly auto-commodifying their fandom. Focussing on how Veronica Mars Kickstarter–related producer and fan activities illustrate multiple circuits of exchange value and use value, I argue that an intensified 'dialectic of value' is in operation here.